PENGARUH PENGGUNAAN MODUL PEMBELAJARAN KONTEKSTUAL BERBASIS MULTIPLE REPRESENTATIONS PADA MATERI FLUIDA STATIS TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA - sigit ardiansyah; Chandra Ertikanto; Undang Rosidin (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
AbstractThis study aims to determine the effect of using contextual learning module based on multiple representations on critical thinking ability. The sample of this research is the students of class X IPA 1 and X IPA 2 SMA Negeri 1 Bandar Surabaya. This research was conducted using Pretest-Posttest Control Group Design type. Data were tested with analysis N-gain, Normality Test, Homogeneity Test and Independent Sample T-test. Based on thetest N-gain, the average value of N-gain critical thinking ability in the experimental class is 0.77 with the high category, while the control class with the medium category is 0.65, so it can be stated that there is a difference of critical thinking ability of the experimental class and class control. Results from the Independent Sample T-test value of the value Sig. (2-Tailed) less than 0.05 is 0.007, then it can be stated there is a significant influence of the use of contextual learning module based on multiple repetitive ntations on students' critical thinking ability.Keywords: Contextual Learning Module, Multiple Represntations, Critical Thinking.